2003
DOI: 10.1016/s0020-7292(03)00265-0
|View full text |Cite
|
Sign up to set email alerts
|

Acetic‐acid guided visual inspection vs. cytology‐based screening for cervical cancer in the Philippines

Abstract: The acetic-acid visualization and VIAM methods are recommended for initial cervical cancer screening in the Philippines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Our results also confirm that the use of a simple low-cost test, such as visual inspection with acetic acid, is acceptable to women. 7,8,31 There is little evidence about determinants of compliance with follow-up treatment in developing countries. 32,33 In our study, the lowest compliance rate was found among unmarried women, those with low levels of education and those with a higher number of pregnancies.…”
Section: Researchmentioning
confidence: 99%
“…Our results also confirm that the use of a simple low-cost test, such as visual inspection with acetic acid, is acceptable to women. 7,8,31 There is little evidence about determinants of compliance with follow-up treatment in developing countries. 32,33 In our study, the lowest compliance rate was found among unmarried women, those with low levels of education and those with a higher number of pregnancies.…”
Section: Researchmentioning
confidence: 99%
“…In an effort to effectively screen and treat more Salvadoran women, BHI, in collaboration with the Ministry of Health (MOH), instituted a single-visit approach using visual inspection of the cervix with acetic acid (VIA) and treatment with cryotherapy. Several studies have concluded that VIA coupled with cryotherapy is an optimal alternative to conventional cytology in resource-poor settings [1][2][3][4][5][6][7]. VIA test qualities are similar to cytology testing (sensitivity 66%-96% and specificity 64%-98%), and cryotherapy has been shown to have an overall cure rate of 89%-91% at 1-year follow up [4,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A review of different studies in India indicated that a simple visual approach involving direct unmagnified inspection of the uterine cervix without acetic acid application ("down staging") was not satisfactory in the early detection of cervical carcinoma and precursor lesions. [11][12][13][14] It has both poor sensitivity and poor specificity in the detection of lesions, particularly preinvasive ones, because there is wide variability in the appearance of the cervix in a population in which obstetric trauma to the cervix is frequent, and in which cervical and vaginal infections are common. But various studies proved that visual inspection of the uterine cervix after the application of 3-5% freshly prepared acetic acid can lead to the satisfactory detection of cervical lesions and lesions missed by cervical cytology.…”
Section: Discussionmentioning
confidence: 99%